Survey perilaku hidup bersih dan sehat anak usia dini di era pandemi covid-19 - Suharti, Sri; Wulan, Sarinah Sri; Fauziah, Edita Izni (THE JOURNAL OF Nursing Management Issues, 2024)
Background: The prevalence of Covid-19 in Indonesia is 927,380 cases. The Covid-19 pandemic can be prevented with PHBS. Clean and healthy living behavior (PHBS) is an activity or activity of living things that can be observed directly or indirectly by outsiders. Purpose: To determine the description of clean and healthy living behavior of early childhood during the Covid-19 pandemic in Purwodadi Village, Gisting District, Tanggamus Regency. Method: This descriptive study involved 30 parents of children aged 4-6 years old, selected using a total sampling technique. Results: The study showed that 90%, or 27 respondents, demonstrated good hygiene and healthy living behaviors, while 10%, or 3 respondents, demonstrated adequate hygiene and healthy living behaviors. The description of hygiene and healthy living behaviors among early childhood children during the COVID-19 pandemic in Purwodadi Village, Gisting District, Tanggamus Regency in 2021 was categorized as good. Conclusion: This study can be continued with a larger number of respondents and can be conducted directly with early childhood respondents.   Keywords: Clean and Healthy Living Behavior; Covid-19 Pandemic; Early Childhood.   Pendahuluan: Prevalensi Covid-19 di Indonesia 927.380 kasus,pandemi Covid-19 bisa di cegah dengan PHBS.Perilaku hidup bersih dan sehat (PHBS) adalah suatu kegiatan atau aktivitas mahluk hidup yang dapat di amati secara langsung maupun tidak langsung yang dapat diamati oleh pihak luar. Tujuan: Untuk mengetahui gambaran perilaku hidup bersih dan sehat anak usia dini di era pandemi Covid-19 di Desa Purwodadi Kecamtan Gisting Kabupaten Tanggamus. Metode: Penelitian jenis deskriptif dengan responden berjumlah 30 orang tua yang memiliki anak usia dini 4-6 tahun yang di ambil menggunakan tekhnik total sampling. Hasil: Penelitian menunjukkan 90% atau 27 responden menunjukan baik perilaku hidup bersih dan sehat sedangkan 10% atau 3 responden menunjukan perilaku hidup bersih dan sehat cukup. Gambaran perilaku hidup bersih dan sehat anak usia dini di era pandemi Covid-9 di Desa Purwodadi Kecamatan Gisting Kabupaten Tanggamus tahun 2021 dalam kategori baik. Simpulan: Penelitian ini bisa dilanjutkan dengan responden yang lebih banyak dan bisa dilakukan dengan responden anak usia dini secara langsung.   Kata Kunci: Anak Usia Dini; Pandemi Covid-19; Perilaku Hidup Bersih Dan Sehat.